IMPROVING LEARNING ACTIVITY AND CONCEP MASTERY OF HYDROCARBON MATERIAL BY IMPLEMENTATION OF EMPIRICAL-INDUKTIVE LEARNING CYCLE - eka romni; nina Kadaritna; Ila Rosilawati (Universitas Lampung, 2012)
Based on observation and interview with chemistry subject teacher in Grade X of State Senior High School 01 Simpang Pematang in Mesuji, the results showed that the average marks of Grade X students’ concept mastery on hydrocarbon material in academic year 2009-2010 was 50.35. The minimum accomplishment criteria established by the school for chemistry was that 100% of students should get more than 62 and only 45% of them got more than 62. The observation results showed that learning process was still dominated by teachers, while students were passive and on taskactivities were low. An effort to overcome this problem was by implementing empirical-inductive learning cycle model in giving hydrocarbon material.The objective of this research was to describe implementations of empirical-inductive learning cycle model to improve: (1) percentage average of on task students’ activities; (2) average of concept masteries; and (3) students’ learning accomplishment. This was a classroom action research which was conducted in three cycles. This research used quantitative data in forms of students’ on task activities, concept masteries, and students’ learning accomplishment.The results showed improvement from cycle 1 to cycle 2 and from cycle 2 to cycle 3 which included: (1) percentage average of each student’s on task activity including asking class mates (6.94% and 12.511% respectively), asking teachers (6.95% and 12.50% respectively), giving opinions (9.72% and 11.11% respectively, answering question (9.72% and 9.73% respectively); (2) concept mastery (8.81% and 7.83% respectively); and (3) student’s learning accomplishment (13.89% and 36.11% respectively ) Therefore, all established performance indicators were achieved.Keywords: empirical-inductive learning cycle, concept mastery, learning accomplishment, on task activity.